Muhammadiyah and Javanese Culture: A Theological Analysis - Jusmiwarti; Marlini T; Ahmad Lahmi; Mursal (Suria Academic Press, 2025)
Muhammadiyah's approach to Javanese culture is often the subject of discussion in the context of the relationship between religion and local traditions. The main problem raised in this research is how Muhammadiyah selects, accommodates, and assimilates Javanese traditions with the Islamic theological principles it promotes. This research aims to analyze Muhammadiyah's theological strategy in responding to Javanese traditions and its contribution to Javanese society at large. The method used in this research is a qualitative method with a descriptive-analytical approach. Data was collected through literature studies from relevant primary and secondary sources, including official Muhammadiyah documents, scientific journals, as well as the results of previous research. The research results show that Muhammadiyah adopts a selective approach to Javanese traditions, maintaining cultural elements that do not conflict with Islamic creeds and modifying certain traditions for the sake of da'wah. This approach produces significant contributions in the fields of education and social and cultural arts, as well as creating harmony between religion and local culture. This study emphasizes the importance of dialogue between universal Islamic values and local wisdom as a basis for building an inclusive and civilized society.